2012
DOI: 10.1016/j.pnpbp.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin system gene polymorphisms are associated with impulsivity in a context dependent manner

Abstract: Impulsivity is a risk factor for adverse outcomes and characterizes several psychiatric disorders and risk for suicide. There is strong evidence that genetic variation influences individual differences in impulsivity, but the details are not yet understood. There is growing interest in better understanding the context dependency of genetic effects that is reflected in studies examining gender specificity, gene×environment interaction and epistasis (gene-gene interaction). In a cross-sectional study we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 79 publications
5
48
0
2
Order By: Relevance
“…It has been supposed that complex behaviours, such as suicidal behaviour, likely show gene-gene interactions (Stoltenberg et al, 2012). Epistatic effects between genes of monoamines and GABA have been found previously in female suicide attempters (Fernández-Navarro et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…It has been supposed that complex behaviours, such as suicidal behaviour, likely show gene-gene interactions (Stoltenberg et al, 2012). Epistatic effects between genes of monoamines and GABA have been found previously in female suicide attempters (Fernández-Navarro et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Several SNPs in the promoter or coding regions of the genes for 5-HT 2A R (HTR 2A ) and 5-HT 2C R (HTR 2C ) have been shown to associate with personality traits, psychiatric conditions, and response to psychiatric medications such as atypical antipsychotics and antidepressants. Impulsivity has been Cocaine, 5-HT 2 Receptors, and Dopamine associated with genotypes that predict reduced 5-HT function (Bjork et al, 2002;Bevilacqua et al, 2010;Stoltenberg et al, 2012;Bevilacqua and Goldman, 2013). The HTR 2A A(-1438)G SNP was associated with response inhibition in two specific behavioral tasks in normal subjects (Nomura et al, 2006) and impulsive behavior in bulimia (Bruce et al, 2005).The HTR 2A T10 2C SNP is associated with impulse control in cocaine-dependent subjects (Bjork et al, 2002).…”
Section: Targeted 5-ht 2a/c Receptor Pharmacotherapy For Cocaine mentioning
confidence: 99%
“…Identification and validation of single nucleotide polymorphisms ( SNPs ) that predict impulsivity, cue reactivity or treatment success could also be useful in guiding prevention efforts (Ducci and Goldman, 2012). Impulsivity has been associated with genotypes that predict reduced 5-HT function (Bevilacqua, et al, 2010; Bevilacqua and Goldman, 2013; Bjork, et al, 2002; Stoltenberg, et al, 2012) and we have recently demonstrated that cocaine-dependent subjects who carry a SNP in the HTR2C (rs6318) (Lappalainen, et al, 1995) predicted to alter 5-HT 2C R functionality (Brasch-Andersen, et al, 2011; Kuhn, et al, 2004; Okada, et al, 2004; Walstab, et al, 2011), exhibit significantly higher attentional bias on the cocaine-word Stroop task. As convergent evidence links genotypes to phenotypes important in addictive processes, it will be possible to best understand the shared genetic liability for impulsivity and cue reactivity, and to integrate this information into more effective clinical care for afflicted patients.…”
Section: Implications For Treatment Of Cocaine Addictionmentioning
confidence: 99%